Polypoidal choroidal vasculopathy and photodynamic therapy with verteporfin - Silva, RM (2005)
BACKGROUND: We evaluated, in a nonrandomised, institutional, prospective study, the efficacy of photodynamic therapy (PDT) with verteporfin in age-related macular degeneration (AMD) eyes with polypoidal choroidal vasculopathy (PCV) and subfoveal exudation. METHODS: A prospective clinical and angiographic study was done in 40 consecutive eyes with PCV treated with PDT using masked best-corrected visual acuity (VA) and fluorescein and indocyanine green angiographic features at baseline and over 2 years. RESULTS: Twenty-one eyes completed 1-year follow-up and showed, after a mean 2.9 PDT sessions, VA improvement in 12 eyes, no change in five eyes, and VA decrease in four eyes. Leakage was absent at the retinal and choroidal level in 14 eyes at 1 year. Recurrence occurred in one eye during the first year. Six eyes completed 2 years of follow-up and showed, after a mean 4 PDT sessions, VA improvement in five eyes and VA decrease in one eye. Leakage was absent at the retinal and choroidal level in five eyes. Recurrence occurred in four of these six eyes during the second year of follow-up. No serious adverse events were observed during the 2 years of follow-up. CONCLUSIONS: PDT with verteporfin was shown to be safe and effective for treating AMD eyes with PCV with subfoveal involvement. VA improvement and absence of leakage were achieved, respectively, in 57.1% and 66.6% of the eyes at 1 year. Recurrences were more frequent during the second year of follow-up.